Penanaman Nilai-nilai Pendidikan Karakter Berbasis Islam di Madrasah Diniyah - Arif Muzayin Shofwan (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The instillation of Islamic-based character education values ​​in Islamic schools (madrasah diniyah) cannot be separated from its function and purpose. This study discusses the instillation of character education values ​​in Islamic schools. The data analysis technique used was content analysis by sorting out things that align with the focus and objectives of the study. This study found that the instillation of Islamic-based character education values ​​in Islamic schools can be achieved through the following books: Taisirul Khallāq Fi Ilmil Akhlāq, Syi’ir Ngudi Susilo and Syi’ir Mitra Sejati, Izzul Adab Alā Ma’āni Mandzumatil Mathlab Libnil Mufawwiq, Washāyal Abā’ Lil Abnā’ Awid Durusil Awwaliyah Fil Akhlāqil Mardliyah, Mandzumah Aqidatil Awam, and Taisirul Khallāq Fi Ilmil Akhlāq. However, the focus of this research is the book Taisirul Khallāq Fi Ilmil Akhlāq, which contains the following character education values, including: developing a pious character; developing a civilized character in the world of education; developing a commendable character within the family, relatives, and neighbors; developing a harmonious character; developing a brotherly character; developing a civilized character in meetings; developing a civilized character when eating, drinking, and sleeping; developing a civilized character in the mosque; developing a character concerned with cleanliness; and others.